Sexual corruption in Bosnia and Herzegovina – Prevalence and legal norms - Mile Šikman; Gorica Ivić (Revija za kriminologiju i krivično pravo)
Sexual corruption is a socially unacceptable behavior that is extremely widespread in society, while at the same time not recognized as such, nor is it directly treated by the positive legislation. The reason for such an attitude can be found in the "normalization" of these behaviors, and consequently their toleration and non-reporting to the responsible authorities. This is a global phenomenon that has a pronounced impact on women and other vulnerable groups, and as such is also present in Bosnia and Herzegovina (BiH). The first question that arises is how widespread this phenomenon is and the ways in which it can be determined. The second question concerns the legal regulation of sexual corruption in the positive legislation, more precisely looking at provisions that already exist in the laws in BiH. In addition, the objective of this analysis is to examine the possibility of integrating the concept of sexual corruption into relevant laws and policies, while establishing a clear distinction compared to other forms of sexual violence. In this way, the awareness of the harmfulness of the mentioned behavior would be raised and the attitude adopted that no one is obliged to suffer sexual corruption and "exercise their rights" or "avoid harmful consequences" in that way.